An Integration of Technology-based Language Teaching (TbLT) with English Language Teaching (ELT) at the tertiary level in Bangladesh - Bipasha, Sharmin Rahman (Loquen, 2025)
This study explores whether technology facilitates language learning at the tertiary level in Bangladesh and whether teachers are proficient enough to teach language through technology. This study also unravels the types of technology used by students and the purpose of using technology in English language learning. This study falls under the qualitative-analytical framework in which the following theories have been used to analyze the field data: drive theory of motivation, instinct theory, engagement theory, and the theory of learner autonomy. In this study, three private universities (located in Dhaka city) were chosen to elicit data from both students and teachers following the technique of snowball sampling. Data from teachers had been elicited through open-ended interviews and data from students had been elicited through three Focus Group Discussions. Fifteen teachers had been interviewed and eighteen participants from three different departments participated in three FGD sessions. The analysis of data suggests that the use of technology helps students learn English which confirms the premise of engagement theory in Technology-based Language Teaching (TbLT); in addition, teachers can teach English using simple technological aids. Besides, students use Android applications and randomly chosen websites to learn vocabulary and syntax which are indicative of drive, instinct, and learner autonomy. Analysis of the data also uncovers that teachers need training on using complex technological devices.